2021
DOI: 10.21203/rs.3.rs-414280/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monkeypox viruses circulate in distantly-related small mammal species in the Democratic Republic of the Congo

Abstract: We determined near complete and complete monkeypox virus genomes in a shrew (Crocidura littoralis), two squirrels (Funisciurus anerythrus, Funisciurus bayonii), and produced shorter sequences from two rats (Stochomys longicaudatus, Cricetomys sp. 2) originating from the Democratic Republic of the Congo. This suggests that a number of rodents besides squirrels (families Muridae and Nesomyidae) and shrews (order Eulipotyphla) are potential monkeypox virus reservoirs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…More recently, more than 80,000 cases have been reported in 2022 worldwide, during an epidemic involving mostly homosexual men [28,29] Local investigations in African countries have suggested that several human MPX cases or epidemics originated from contacts with wild mammals, such as chimpanzee (Pan troglodytes), Pennant's red colobus (Piliocolobus pennanti) or Gambian pouched rat (Cricetomys emini) [30,31]. In agreement with that, MPXV has been isolated or sequenced from several mammal species in Africa, including arboreal species, such as monkeys and squirrels, as well as ground-living species, including rodents and shrews [32][33][34][35][36][37]. In addition, antibodies against OPXV were detected in many species from four mammalian orders and nine families.…”
Section: Introductionmentioning
confidence: 74%
“…More recently, more than 80,000 cases have been reported in 2022 worldwide, during an epidemic involving mostly homosexual men [28,29] Local investigations in African countries have suggested that several human MPX cases or epidemics originated from contacts with wild mammals, such as chimpanzee (Pan troglodytes), Pennant's red colobus (Piliocolobus pennanti) or Gambian pouched rat (Cricetomys emini) [30,31]. In agreement with that, MPXV has been isolated or sequenced from several mammal species in Africa, including arboreal species, such as monkeys and squirrels, as well as ground-living species, including rodents and shrews [32][33][34][35][36][37]. In addition, antibodies against OPXV were detected in many species from four mammalian orders and nine families.…”
Section: Introductionmentioning
confidence: 74%
“…MPXV has been detected in a variety of hosts including in 1985 from Thomas's rope squirrel (Funisciurus anerythrus) in the Democratic Republic of the Congo (DRC), 15 in 1992 from a sooty mangabey monkey (Cercocebus atys) in Côte d'Ivoire, 16 in 2010-2016 from rope squirrels (Funisciurus anerythrus, Funisciurus bayonii), other rodents species (Stochomys longicaudatus, Cricetomys sp.) and one shrew (Crocidura littoralis) in DRC, 17 in 2019 in chimpanzee (Pan troglodytes verus) faeces in Taï National Park, Côte d'Ivoire, 18 from Gambian giant pouched rats (Cricetomys gambianus), 19,20 and from African dormouse (Graphiurus kelleni). 21 cases annually since 2005.…”
Section: The Pathogenmentioning
confidence: 99%
“…Host and tissue tropism: Members of the OPV family are thought to exhibit diverse spectra of host tropisms[ 46 ]. Although the reservoir host for MPXV has not been definitively identified, many mammalian species are naturally infected with MPXV[ 47 ]. Thus, it is believed that MPXV has a wide host range.…”
Section: Infection Biology Diagnosis and Treatmentmentioning
confidence: 99%